A study on perceived gender discrimination, job satisfaction, interpersonal trust and turnover intention in private banks of Pakistan - Syeda Mahera Husain (2018)
The main aim of this thesis is to investigate and measures the effect of gender discrimination on female's employees in private banks of Pakistan. The study examine the perception of Pakistani working women againts gender discrimination and highlights the research gap as how women are paid less and underrepresented in most influential positions. It further discusses the relationship of gender discrimination on employee job satisfaction level, trust on organization and how the productivity of the firm is reduced which results in employee intention to quit the organization. The study also investigate the mediating effect of job satisfaction between gender discrimination and employee turnover intention. A total set of 237 questionnaires were used for the statistical data requirement. Based on quantitative research approach the data analysis is done by using IBM SPSS Statistics 22 and Smart PLS software version 3.0. Bootstrapping is conducted from the collected statistical data, which shows a mediating effect between gender discrimination, employee turnover and job satisfaction. The software is used to assess convergent validity, discriminant validity, cross loading and hypotheses. The results interestingly shows that 4 out of 5 hypotheses are significantly correlated at p<0.01. In addition, results indicate that gender discrimination has a significant influence on employee job satisfaction level, turnover intention but trust of employee over organization is not affected. Firms can reduce gender discrimination by giving equal opportunities to the employees. The outcomes of this study clearly manifest a considerable amount of discrimination present in the organizations. Therefore, it is highly recommended for the stakeholders to implement anti-discriminatory policies in order to strengthen the legal framework of the organization. Managers need to be proactive and prevent gender discrimination from occurring in the first place to accomplish organizational goals.